MOTIVASIDANHASILSTUDISISWAMISKINSMPNEGERI3KECAMATAN PUJUD - Budi Pramaharja Budi Pramaharja; Zulfan Saam Zulfaan Saam; Tri Umari Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstractMotivation and study result of SMPN 3 PUJUD’s poor students: Budi Pramaharja, 1205188179, 2014. Study program: guidance and counseling; science department, Education and science faculty: Riau University. Counselor I: Prof. Dr. Zulfan Saam, M. Si; Counselor II: Dra. Tri Umari, M. Si.This research aims to know the illustration of poor student’ study motivation in SMPN 3 PUJUD that back grounded by some reason that seen in school such as : the problem about low motivation and the study result of poor student in SMPN 3 PUJUD.The method that be used in this research is Descriptive method in percentage, the location of research is in SMPN 3 PUJUD. This research subject is VII, VIII, IX students’ class. Giving the study motivation is taken by sample technique or saturate sample. Because the sum of population in this research is small. Data and the instrument of data collection is questionnaire form about motivation and study of result poor student in SMPN 3 PUJUD that done by researcher and be guided at lattice work with the alternative of multiple choices: frequent, often, sometimes, seldom and never. Data analysis technique uses the percentage formula (Anas Sudijono, 2004:170)Based on the research and data processing that had been done, can be resumed : (1) based on the result of data processing can be know the general descriptive of study motivation: VII, VIII, IX students’ class of SMPN 3 PUJUD, PUJUD district, school year 2013-2014, that is by paying attention the intensity of giving the poor students’ study motivation, with the result that low level category. The poor students’ study motivation is be categorized low level, be market by : a) have not the lesson book, b) less the parent’s attention, c) seldom visit the library, d) less the media in giving the assist to the development of potential students in studying, so that become the adult human and responsible. (2) the description of poor students’ study result in SMPN 3 PUJUD can be know that is the students of VII, VIII, IX class, school year 2013-2014, low level dominantly . the low subject is under KKM on Pendidikan Pancasila dan Kewarganegaraan (citizen) lesson by rating 47,5 before remedial, and on IPA (science) lesson by rating 45 before remedial. (3) constraints that be faced by the poor students like as helping parent, long distance from house to school, this case result the low study motivation and study result for students. Keywords: Students motivation, students learning process